2018
DOI: 10.1016/j.jtho.2018.08.923
|View full text |Cite
|
Sign up to set email alerts
|

P1.14-21 Circulating Biomarkers in Thymic Epithelial Tumors

Abstract: MAVS pathway by direct administration into the tumor. We performed the phase I dose escalation safety/tolerability and preliminary efficacy study of intra-tumoral and subcutaneous administration of HVJ-E in patients suffering from chemotherapy-resistant malignant pleural mesothelioma. Method: We performed the dose upward titration clinical study for checking the safety, drug tolerance, and preliminary efficacy of the intra-tumoral and subsequent subcutaneous administration of HVJ-E. We administrated HVJ-E to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…in the analysis of 90 patients diagnosed with stage III or IV thymic cancer (LDH 190 U/L – relative risk of death 2.7; P = 0.004) 28 and Valdivia et al . who showed a very clear tendency for increase of LDH activity among patients with stage IV thymic carcinomas, according to the Masaoka classification 10 . The studies involving patients with other cancers of the chest area also confirmed the prognostic value of increased LDH activity 29,30 …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…in the analysis of 90 patients diagnosed with stage III or IV thymic cancer (LDH 190 U/L – relative risk of death 2.7; P = 0.004) 28 and Valdivia et al . who showed a very clear tendency for increase of LDH activity among patients with stage IV thymic carcinomas, according to the Masaoka classification 10 . The studies involving patients with other cancers of the chest area also confirmed the prognostic value of increased LDH activity 29,30 …”
Section: Discussionmentioning
confidence: 76%
“…Additionally, resection radicality, clinical stage and histological type are, together with the initial tumor size, the risk factors for disease recurrence after surgery 9 . There have also been reports of the prognostic value of the so‐called circulating biomarkers (C Reactive Protein – CRP and lactate dehydrogenase – LDH), 10 as well as the importance of the neutrophil‐to‐lymphocyte ratio (NLR) 11 for survival and prognosis.…”
Section: Introductionmentioning
confidence: 99%